Translation between Untranslatability and Appropriation - BADAOUI, Bouchra (International Journal of Linguistics and Translation Studies, 2024)
This paper delves into the complexities of translation by examining the interplay between untranslatability and appropriation. Using the theoretical frameworks of scholars such as Walter Benjamin, Jacques Derrida, and Roman Jakobson, it highlights the inherent challenges of conveying linguistic, cultural, and contextual nuances from a source text into a target language. Simultaneously, it explores the notion of translation as appropriation, guided by the critical perspectives of Lawrence Venuti, André Lefevere, and Gayatri Spivak. The analysis is contextualized through Moroccan cinema, focusing on Moumen Smihi’s El Chergui (1975) and Abdelkader Lagtaa’s Hubb fi al-Dar al-Baida (Love in Casablanca, 1991). These films illustrate how untranslatability and appropriation manifest in cinematic expressions, emphasizing the political, cultural, and ethical dimensions of translation.